2011
DOI: 10.1590/s1413-81232011000800029
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência da síndrome metabólica e seus fatores associados em área rural de Minas Gerais (MG, Brasil)

Abstract: Prevalência da síndrome metabólica e seus fatores associados em área rural de Minas Gerais (MG, Brasil)Prevalence of metabolic syndrome and its associated factors in a rural area of Minas Gerais State (MG, Brazil)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
1
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 21 publications
4
42
1
9
Order By: Relevance
“…Another study reports similar data in a rural population of the Jequitinhonha Valley -MG (33.6% women vs. 7.7% men). 8 By analyzing the prevalence of MS, we found 3.07 times more likely to have the MS among the female public, as compared to men. In the age group 75-79 years comes to 5.8 times more likely to have the syndrome.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Another study reports similar data in a rural population of the Jequitinhonha Valley -MG (33.6% women vs. 7.7% men). 8 By analyzing the prevalence of MS, we found 3.07 times more likely to have the MS among the female public, as compared to men. In the age group 75-79 years comes to 5.8 times more likely to have the syndrome.…”
Section: Discussionmentioning
confidence: 78%
“…6 Is important to highlight the association of MS with cardiovascular disease, increasing overall mortality rate of approximately 1.5 times and cardiovascular mortality at 2.5 times. 6 Many studies 2,[7][8][9] highlight that aging predisposes the increase of conditions to the development of certain risk factors including central obesity, dyslipidemia, insulin resistance and hypertension. Nevertheless, the impact between the place of residence, characterized as urban and rural areas, also appear to influence the incidence of risk factors and quality of life of the resident population in these two locations.…”
Section: Introductionmentioning
confidence: 99%
“…16,18 Dos indivíduos acompanhados 16,17% (n=11) apresentaram SM, ou seja, possuem fatores usualmente relacionados à deposição central de gordura e a resistência à insulina. Dados semelhantes foram encontrados por Pimenta et al, 19 que avaliaram a prevalência de SM e seus fatores associados em uma área rural de Minas Gerais, observando uma prevalência 14,9%.…”
Section: Resultsunclassified
“…In the studied sample, decreased concentrations of HDL-C occurred in 18.8% of the school in CSEB, a result that is higher than that of the cross-sectional study done among children and adolescent who were born in Sāo Paulo State, which totaled 13.8% 37 . The presence of MS was diagnosed in 8.7% and all of CSEB and studies indicate the prevalence of those affected to be between 4.1% and 17.2% of investigated [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] . The relationship between CSE and MS is close because economic disadvantages are predictive for its occurrence among children and adolescents 6,7,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Two basic health units in the city of São Paulo -SP were investigated regarding the relationship of MS and CSE, it was found that residents in the neighborhood of those with low economic means have 2.3 times the risk of developing MS 10 . In a population-based study in rural communities, using Jequitinhonha Valley, with 534 individuals with limited socioeconomic resources, it was revealed that women are more prone to the occurrence of chronic diseases because they have higher rates of physical inactivity, obesity and metabolic changes 11 . The relationship between CSE and MS has been little explored in epidemiological investigations, but economic disadvantages are predictive for the incidence of CVD morbidity and mortality [12][13][14] .…”
mentioning
confidence: 99%